7 Bottoms towards an Ecotourism Icon: Environmental Communication Studies in Ecotourism Areas - HASMIRA, Mira Hasti; BARLIAN, Eri; FRINALDI, Aldri; DEWATA, Indang; FATIMAH, Siti; PUTRA, Aprizon (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023DO - 10.14505/jemt.v14.3(67).25, 2023)
This paper describes the meaning and naming of the destinations that are passed to the icon of an ecotourism location. This interpretation aims to provide input to ecotourism guides about the messages they must convey when guiding ecotourists. The environmental components they encounter along the way are important materials that must be presented to eco-tourists. Communication must be seen not only as one of the supporting elements for environmental management but as an integral part of environmental management. As is the case in the management and development of ecotourism. The role of ecotourism guides is very important when guiding ecotourists. Ecotourism activities are communicative events and forms of experience on how to understand ecotourism itself.